2011
DOI: 10.1111/j.1445-6664.2011.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference and economic threshold of horse purslane (Trianthema portulacastrum) in soybean cultivation in northern India

Abstract: Soybean is the most important oilseed crop that is grown in India. Horse purslane (Trianthema portulacastrum L.) infests soybean heavily, causing enormous yield losses and threatening the sustainability of the soybean production system. Information on the interference and economic threshold of horse purslane will be useful for the effective management of horse purslane in soybean. This will lead to the rationalization of herbicide use and the reduction of herbicide input into the environment. It was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
(37 reference statements)
1
25
0
1
Order By: Relevance
“…For example, soybean yield infested with Cyperus rotundus (0-200 pl•m -2 ) was decreased by 47% (Das et al 2014), while soybean yield loss can reach 21% due infestation with Trianthema portulacastrum (0-200 pl•m -2 ) (Hazra et al 2011). Bidens spp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, soybean yield infested with Cyperus rotundus (0-200 pl•m -2 ) was decreased by 47% (Das et al 2014), while soybean yield loss can reach 21% due infestation with Trianthema portulacastrum (0-200 pl•m -2 ) (Hazra et al 2011). Bidens spp.…”
Section: Introductionmentioning
confidence: 99%
“…Balyan and Malik (1989) reported that horse purslane is a strong competitor, reducing the yield of mung bean by 50 to 60% when left untreated. Significant losses in maize, soybean and peanut yield are also attributed to this weed (Grichar, 1993 and2008;Hazra et al, 2011;Saeed et al, 2010). Allelopathic growth inhibition of crop plants from horse purslane infestation has also been reported (Sethi and Mohnot 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It is a weed of cultivated fields and waste lands. It grows luxuriantly if water is available and it is especially problematic in maize, cotton, potato, sugarcane, pulses, fodders and vegetables, particularly during rainy season (Hazra et al, 2011). Its prostrate growth and profuse branching capacity helps it to quickly cover the soil surface and form a green carpet (Senthil et al, 2009).…”
Section: Introductionmentioning
confidence: 99%